(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The article considers the specifics of energy-efficient construction in the regional markets of real estate of Ukraine and the factors affecting it. Analyzed the work of scientists who have studied this issue shows the degree of its illumination. It identifies topical problems of development of the market for energy efficient real estate in Ukraine is investigated and its regional aspects. Based on the experience of the countries of the European Union analyzes the main trends and patterns of development energy-efficient construction. To identify the mechanism of financing energy-efficient construction and housing modernization in foreign countries. The directions of the state policy of Ukraine, which precede the implementation of energy efficient construction. Today, one of the main priorities and objectives of energy policy of Ukraine is energy-saving. Despite the relevance of this topic, improvements are observed only at a granular level, and the use of energy is excessive. The real estate market is one of the components of the state economy, as it carries more than half the world’s wealth, and its stable operation is considered to be one of the most complex processes of market transformations occurring in the state. Also, today the pressing issue is the efficient use of energy resources and use of renewable sources of energy. The development of these areas will improve conditions for small and medium business, creation of new jobs and improve the economy of the country. In Ukraine there are several problems that hinder the development of energy-efficient construction, among which the lack of a legal and regulatory framework in this area, low interest of various participants of the construction market in the introduction of this concept, the absence of the state comprehensive vision for solving this problem, and the like. In world practice, accumulated a large number of mechanisms and tools that will effectively implement the principles of «green» construction throughout the state. It is necessary to address the important issue regarding the implementation of Ukraine’s obligations as a full member of the Energy community to implement in national legislation the requirements of Directive 2010/31/EU «On the energy performance of buildings». The main problems for construction enterprises are: production of highly insulating materials, implementation of energy efficient technologies at the stage of construction of new residential buildings, the use of modern engineering networks and systems, equipment, metering devices, and thermal modernization of the existing housing stock. It is also necessary to develop a program to support banks and to work with regional administrations regarding the program, payment of percent on the credits and consider other mechanisms for financing energy efficiency projects for the population.